The physiological effects of orlistat and efficiency extract of cinnamon on body weight and lipid profile in obese male rats - Benan Aad abed; Wafaa Kadhim Jasim; Tuqa Sabbar Rahi (Journal of Kerbala for Agricultural Sciences, 2024)
The purpose of the current study was to examine the adverse effects of orlistat used alone and in combination with cinnamon with regard to weight gain, body weight percentage, and alterations in the lipid profile in male rats that were obese. Have been selected There were two groups of adult male rats. First experience (induction obesity) for six weeks to induce obesity into (Control group : 10 rats received only rats normal diet without fat as a daily dose) and (High fat diet group : 30 rats received only fed with high-fat diet contain Plate with soy fat and introduce as daily dose) , After this period (six weeks) weight gain and second main groups to ensure the induction , Second experience for six weeks , The treatment period lasted from week 6 to week 12 after confirming the induction of obesity daily oral dosing with the fallowing groups) Control group : 10 rats received only rats normal diet without fat as a daily dose , High fat diet group : 30 rats after induction of obesity divided into the following:-A) Group high fat diet with orlistat 10 rats (10 mg/kg/day). B) Group high fat diet with cinnamon 10 rats (100 mg/kg BW). C) Group high fat diet with orlistat (10 mg/kg/day ) and cinnamon (100 mg/kg BW) 10 rats. The findings show that Weight gain were increase in a significant value (P<0.05) in fat group comparatively to control group and orlistat group , cinnamon group , combination mix group While cholesterol , Triglycerides , LDL-c and VLDL-c were increase in a significant value (P<0.05) while showed a significant (P<0.05) decrease in HDL-c in fat group comparatively to control group and orlistat group , cinnamon group , combination mix group , Conclusions In addition to its ability to inhibit pancreatic lipase, orlistat can also be used to control weight because it indirectly reduces appetite by raising glucagon, IDE, and dopamine levels and by inhibiting the glutamate neurotransmitter. Meanwhile, cinnamon improves blood sugar levels and glycaemic targets.